Research on mafias and the fragmentation of scientific disciplines (Rivista di Studi e Ricerche sulla criminalità organizzata, 2025)
The increasing fragmentation of scientific research represents a critical issue across multiple disciplinary domains. This article explores the phenomenon through the lens of mafia studies, highlighting how current academic validation logics—based on selective and sectoral criteria—hinder the development of interdisciplinary and transnational approaches. These recognition mechanisms, often rigidly normative, not only restrict the circulation and integration of knowledge, but also undermine the possibility of constructing a broad and shared cultural discourse.
Keywords: mafia; antimafia; research; scientific journals; internationalization